2013
DOI: 10.3109/07420528.2013.800874
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Sleepiness, and Neurobehavioral Performance While on Watch in a Simulated 4 Hours on/8 Hours off Maritime Watch System

Abstract: Seafarer sleepiness jeopardizes safety at sea and has been documented as a direct or contributing factor in many maritime accidents. This study investigates sleep, sleepiness, and neurobehavioral performance in a simulated 4 h on/8 h off watch system as well as the effects of a single free watch disturbance, simulating a condition of overtime work, resulting in 16 h of work in a row and a missed sleep opportunity. Thirty bridge officers (age 30 ± 6 yrs; 29 men) participated in bridge simulator trials on an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…The studies examined in this review employed a range of schedules, which can be broadly divided into: (i) work/rest schedules, such as 4 hours-on/8 hours-off, 6 hours-on/6 hours-off and 8 hours-on/8 hours-off sched- The last seven days at sea were used in the analyses 6h-on/6-off : TST was similar for both watch rotations 4h-on/8h-off: TST was higher for team one followed by team three then team two watch rotations TST was shorter, frequency of nodding while on duty and excessive daytime sleepiness was higher on 6h-on/6-off compared to 4h-on/8h-off watch systems (24); and (iii) work/ rest schedules that incorporate a swing shift, "dog" shift, layover or disruption, typically in the middle of a roster schedule (22,23,29,33,37). Five studies examined 8 hours-on/8 hours-off roster schedules, all of which were conducted with Australian train drivers (22,25,29,36,37), five examined 6 hours-on/6 hours-off shift schedules, predominantly in ship bridge officers and offshore fleet workers (17,23,30,34,39), and nine examined 4 hours-on/8 hours-off shift schedules all among maritime watch keepers (17, 26-28, 30-33, 35).…”
Section: Schedules and Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies examined in this review employed a range of schedules, which can be broadly divided into: (i) work/rest schedules, such as 4 hours-on/8 hours-off, 6 hours-on/6 hours-off and 8 hours-on/8 hours-off sched- The last seven days at sea were used in the analyses 6h-on/6-off : TST was similar for both watch rotations 4h-on/8h-off: TST was higher for team one followed by team three then team two watch rotations TST was shorter, frequency of nodding while on duty and excessive daytime sleepiness was higher on 6h-on/6-off compared to 4h-on/8h-off watch systems (24); and (iii) work/ rest schedules that incorporate a swing shift, "dog" shift, layover or disruption, typically in the middle of a roster schedule (22,23,29,33,37). Five studies examined 8 hours-on/8 hours-off roster schedules, all of which were conducted with Australian train drivers (22,25,29,36,37), five examined 6 hours-on/6 hours-off shift schedules, predominantly in ship bridge officers and offshore fleet workers (17,23,30,34,39), and nine examined 4 hours-on/8 hours-off shift schedules all among maritime watch keepers (17, 26-28, 30-33, 35).…”
Section: Schedules and Participantsmentioning
confidence: 99%
“…Eight of the studies identified in this review used a within-subject's design (18,22,23,25,29,(36)(37)(38), ten a between-subject's design (17,24,26,27,30,31,34,35,39,40), and four employed a mixed within-and between-subjects design (19,28,32,33). Seventeen studies were field-based (17-19, 22, 24-32, 34-37) and five used laboratory simulations (23,33,(38)(39)(40).…”
Section: Schedules and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other field research comparing the 3/9 watch schedule to a 6/6 watch schedule (Shattuck and Matsangas, 2014) or a 5/10 watch schedule (Shattuck et al, 2015) also identifies the 3/9 watch schedule as more effective for maintaining psychomotor vigilance. That said, even non-rotating watch schedules are associated with performance impairment, depending on the time of day, as was recently demonstrated in a simulated 4/8 watch schedule (van Leeuwen et al, 2013).…”
Section: Performance Resultsmentioning
confidence: 56%